Information System for Supporting Seafarer's Health Incident Reporting...International Conference on Informatics, Management, and Technology in Healthcare (ICIMTH) (Virtual), December 13-15, 2024 - KARITIS, Konstantinos; ZOULIAS, Emmanouil; LIASKOS, Joseph; MANTAS, John (Studies in Health Technology & Informatics, 2025)
This research studies and develops an information support system for recording health incidents at sea in T.M.A.S. (Telemedical Maritime Assistance Services) Telemedicine centres. The T.M.A.S. are Telemedical consulting services designed to help and support seafarers and passengers on board ships. Various means of communication are used to aid, such as marine radio, email, landline, mobile or satellite telephones, or facsimile, when the ship is days or even hours away from the nearest port and at distances that make direct transit impractical or impossible. In Greece, the M.A.C. (Medical Advice Centre) was established in 1987, mainly for merchant ships, fishing vessels, and pleasure craft of all categories, regardless of flag, place of sailing, or nationality. In this paper, an Internet Information System was developed to support recording health incidents at sea, as these are legally required to be recorded in the M.A.C. The system was developed using the Anvil tool and the Python programming language.